Optimalisasi Sumber Daya Sekolah untuk Penguatan Ekstrakurikuler yang Kreatif dan Inspiratif Bagi Siswa Sekolah Dasar - Sri Marmoah; Jenny Indrastoeti Siti Poerwanti; Supianto Supianto; Sukarno Sukarno; Siti Istiyati (DEDIKASI: Community Service Reports, 2025)
Extracurricular activities in primary schools play an important role in supporting the development of student's interests, talents, and character. SD Negeri Purwotomo faces challenges in attracting new students due to the lack of attractive extracurricular programs and school promotions. This service activity aims to strengthen extracurricular programs by optimizing school resources, training in social media management, and mentoring creative and inspiring extracurricular programs. The service method is carried out in three stages: planning, implementation, and evaluation. As a result, five interest-based extracurricular programs were successfully developed: computer (editing and design with Canva), English (reading and writing), reading and writing the Qur'an (BTA), and arts (karawitan and singing). This activity also produced attractive school promotional digital content and increased student participation in the learning process. This activity proves that collaboration between schools, students, and the education community can create a more dynamic learning environment and support student character development.